Your inner hedgehog : a Professor Dr. von Igelfeld entertainment novel - McCall Smith, Alexander, 1948- (McCall Smith, Alexander, 1948- Professor Dr. von Igelfeld entertainment novel., 2021)
Professor Dr. Moritz-Maria von Igelfeld and his colleagues at the University of Regensburg's Institute of Romance Philology pride themselves on their unwavering commitment to intellectual excellence. They know it is their job to protect a certain civilized approach to the scholarly arts. So when a new deputy librarian, Dr. Hilda Schreiber-Ziegler, threatens to drag them all down a path of progressive inclusivity, they are determined to stop her in the name of scholarship--even if that requires von Igelfeld to make the noble sacrifice of running for director of the Institute. Alas, politics is never easy, and in order to put his best foot forward, von Igelfeld will be required to take up a visiting fellowship at Oxford and cultivate the attentions of a rather effusive young American scholar. Still, von Igelfeld has always heeded the clarion call of duty, especially when it comes with a larger office.--